The Role of Context in Focus on Grammar - Nassaji, Hossein; Fotos, Sandra S. (Teaching Grammar in Second Language Classrooms, 2011)
In this chapter, we discuss the role of context in communicative focus on grammar. An important factor to consider in using FonF methods to teach grammar communicatively is the context of the instructional situation. For example, is it a second language or a foreign language context? In other words, is the target language a second language, spoken in the country where the learner resides, or is it a foreign language, studied in the learner’s home country? There are a number of other contextual factors that have important implications for teaching grammar. Is the teacher a native speaker (NS) of the target language or a non-native speaker (NNS)? What about the age of the learner? Is the learner a child, able to learn language quickly and easily perhaps due to a language acquisition device (Chomsky, 1965), or is the learner post-puberty, or an adult, needing to learn through a more cognitive approach? How does the teaching of EFL ﬁt in to the growing body of literature on World Englishes (Burns & Coﬃn, 2003; Jenkins, 2003)? Regarding the instructional situation, is the L2 learner studying in an immersion program with carefully selected content instruction in the L2 and considerable support for both L1 and L2 learning? Or is the learner mostly in the regular L2 program for NSs, with need for L2 instruction met through “pull-out” extra language classes? Or is the learner studying in a simpliﬁed contentbased system taught in easy and simpliﬁed L2 with the goal of rapidly mainstreaming the learner into regular NS classes? Or is the L2 learner simply submerged in regular L2 classes with no L2 support at all?